Increased expression of genes in a radioresistant cell strain: modulation of hnRNP E2, Hsp90 and SSBP2 genes in γ-irradiated Chinese hamster V79 cells. (25th March 2008) - Roychoudhury, Paromita; Pandit, Bhaswati; Pathak, Rupak; Chaudhuri, Keya; , Nitai P. Bhattacharyya
The methotrexate-resistant cell strain M5, derived from Chinese hamster lung fibroblast cell line V79, provides a good model to study differential gene expression in response to stress. Genes coding for human homologues of myosin phosphatase (AF458589), filamin-like protein (AAA92644), phosphate transporter 1 (AAH199441) and hnRNP E2 (NP_035172.1) were upregulated in M5 as determined by RAP-PCR. The Gene Expression Array (GEArray) analysis showed increased expression of caspase-6 and Hsp90 in M5 cells compared to that observed in V79 cells. Genomic amplification of SSBP2 as well as its transcriptional upregulation was also detected in M5 cells. Following γ-irradiation, expressions of SSBP2, Hsp90 and hnRNP E2 increased steadily in V79 cells. However, expression of hnRNP K and hnRNP A2 genes decreased at first and then increased, while hnRNP C1 gene expression remained unaffected up to the time studied. Thus, SSBP2, Hsp90 and hnRNP E2 are involved in the radiation response of V79 cells.